Comprehension of Pelvic Organ Prolapse and Urinary Incontinence in Southern Appalachian Women. Issue 1 (January 2018) - Hobdy, Danielle; Huffaker, R. Keith; Bailey, Beth
Abstract : Objectives: Despite their growing prevalence, pelvic floor disorders (PFDs) remain undertreated and not well understood by patients, with treatment disparities noted in specific subgroups of women. The goal of the present study was to determine the basic understanding of PFDs of women in the southern Appalachian region of the United States, to determine factors that predict knowledge, and to explore the possible disparities in seeking access to care among women in this region who reported symptoms. Methods: A survey of patient knowledge of PFDs, specifically urinary incontinence (UI) and pelvic organ prolapse (POP), was conducted in Johnson City, Tennessee, and involved 305 female patients from this city and the surrounding region. Results: Almost half of the participants (43%) reported UI symptoms, with only 25% of these participants reporting treatment. A much smaller percentage (5%) reported POP symptoms, but 44% reported receiving treatment. Overall proficiency for UI knowledge was 54.4%, and 69.5% for POP knowledge. Higher UI knowledge was predicted ( P < 0.05) by age younger than 60 years, annual income >$50, 000, more than a high school education, and being married. UI knowledge was unrelated to the presence of UI symptoms, receipt of UI treatment, or having seen a urospecialist. Higher POP knowledge was predicted ( P < 0.05) by annual income >$50, 000, more than a high school education, and presence of POP symptoms. The only factor significantly predicting seeking treatment among women with UI symptoms was marital status. Conclusions: Overall knowledge of both UI and POP was reasonably high in this population, suggesting appropriate self-education or education by providers in the region. The women most affected by UI, particularly those older than 60 years, were not well informed, and education by providers does not appear to specifically target women seeking treatment. We must continue to educate and further reduce the gap of knowledge and treatment regarding PFDs in southern Appalachia. Abstract : This was a cross-sectional study of a survey of 305 women in the southern Appalachian region of the United States regarding their knowledge of pelvic floor disorders, with the purpose of determining how well the authors were educating their patient population. The Prolapse and Incontinence Knowledge Questionnaire was used to measure patient understanding.